2020
DOI: 10.3390/cells9122641
|View full text |Cite
|
Sign up to set email alerts
|

The Collagen-Based Medical Device MD-Tissue Acts as a Mechanical Scaffold Influencing Morpho-Functional Properties of Cultured Human Tenocytes

Abstract: Mechanotransduction is the ability of cells to translate mechanical stimuli into biochemical signals that can ultimately influence gene expression, cell morphology and cell fate. Tenocytes are responsible for tendon mechanical adaptation converting mechanical stimuli imposed during mechanical loading, thus affecting extracellular matrix homeostasis. Since we previously demonstrated that MD-Tissue, an injectable collagen-based medical compound containing swine-derived collagen as the main component, is able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
3
7
1
Order By: Relevance
“…These data were in line with previously published data, which, using the same collagen-based injectable medical device as a coating, demonstrated increased viability and substrate attachment of human tenocytes, known specialized fibroblasts of tendons [ 39 , 40 ]. On the contrary, other authors have found no advantages in the use of a collagen coating, demonstrating that fibroblasts (in this case human skin fibroblasts), grown on collagen-coated dishes, were rounder in shape and with a shorter perimeter, compared to those grown on uncoated polystyrene or glass culture dishes [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data were in line with previously published data, which, using the same collagen-based injectable medical device as a coating, demonstrated increased viability and substrate attachment of human tenocytes, known specialized fibroblasts of tendons [ 39 , 40 ]. On the contrary, other authors have found no advantages in the use of a collagen coating, demonstrating that fibroblasts (in this case human skin fibroblasts), grown on collagen-coated dishes, were rounder in shape and with a shorter perimeter, compared to those grown on uncoated polystyrene or glass culture dishes [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, other authors have found no advantages in the use of a collagen coating, demonstrating that fibroblasts (in this case human skin fibroblasts), grown on collagen-coated dishes, were rounder in shape and with a shorter perimeter, compared to those grown on uncoated polystyrene or glass culture dishes [ 50 ]. Furthermore, the number and density of cells at confluence were not affected by that specific collagen coating as well, but it should be probably considered that the fibroblast’s origin and the type of collagen used for their experimentation were different from those used in the present study and in the study conducted by Randelli et al [ 40 ].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In addition to being the main structural element of the extracellular matrix of human tissues, type I collagen also has numerous intrinsic properties, such as biocompatibility for many biological applications, bioactivity, biodegradability, and the ability, in its native form, to generate hydrogels, by a simple pH change [ 41 , 42 , 43 , 44 , 45 , 46 ]. Due to these important characteristics, it receives great attention in the biomedical field, both as a functional ingredient in different formulations and as a component of several products, such as medical devices and pharmaceutical systems [ 46 , 47 , 48 , 49 ]. Although collagen appeared in the first phase of evolution in primitive animals such as jellyfish, corals and sea anemones, the mammalian (especially bovine and porcine) form is the main source used in the industrial and biomedical fields [ 50 , 51 , 52 ].…”
Section: Collagen Characterizationmentioning
confidence: 99%